Analisis Keberlanjutan Usaha Mikro, Kecil, dan Menengah UMKM di Tengah Tantangan Ekonomi Digital Kota Medan - Zarin Zakkiatul Fauziah; Cindy Rahmawati; Nayla Salsabila; Raysha Zahra Rigandi; Tamara Icha Nadine Saragi Turnip (FEB Universitas Maritim Semarang, 2025)
MSMEs play a key role in the national economy, especially in increasing economic growth and creating new jobs. However, in the digital era, MSMEs face major problems, such as low levels of digital literacy, limited access to the internet, and fierce competition with large companies that have used technology before. This study examines the variables that influence the sustainability of MSMEs amidst digital challenges and finds methods that can be used so that MSMEs can survive and grow. The research method was carried out through surveys and direct interviews with MSME actors at Pasar Pagi Setia Budi, Medan, North Sumatra. The results of the study showed that most MSME actors did not utilize digital platforms for marketing and transactions, which resulted in decreased income. To increase competitiveness, MSMEs need to improve their digital knowledge, adopt online marketing strategies, and optimize the use of e-commerce and social media. Support from the government, financial institutions, and technology companies is also very important. In the increasingly competitive digital era, by implementing the right digitalization strategy, MSMEs can improve operational efficiency, expand market reach, and maintain the sustainability of their business.